2004
DOI: 10.1109/tbme.2004.824123
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel Magnetic Stimulation System Design Considering Mutual Couplings Among the Stimulation Coils

Abstract: We introduce some simulation and experiment results of the multichannel magnetic stimulator development that has been carried out as an initial attempt to realize a multichannel functional magnetic stimulator. For efficient functional magnetic stimulations, precise spatial localization of stimulation sites without any movements of the stimulation coils is very important. We have found that the mutual coupling effect among the adjacent stimulation coils in the coil array has to be considered in the determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Other designs such as single-layer coil arrays have no way to address dead zones, and even other multi-layer arrays do not have full control over the current direction, so they are not able to fully manipulate the return currents. Proximity effects such as mutual coupling [29], degraded Q and distorted current waveforms, caused by coil to coil interaction, are mitigated by our ability to power down, ground non-energized coils and control individual coil current levels. This bears further study and is being reported in a forthcoming paper.…”
Section: B Excitation Principles Using Multi-coil or Dense Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Other designs such as single-layer coil arrays have no way to address dead zones, and even other multi-layer arrays do not have full control over the current direction, so they are not able to fully manipulate the return currents. Proximity effects such as mutual coupling [29], degraded Q and distorted current waveforms, caused by coil to coil interaction, are mitigated by our ability to power down, ground non-energized coils and control individual coil current levels. This bears further study and is being reported in a forthcoming paper.…”
Section: B Excitation Principles Using Multi-coil or Dense Arraysmentioning
confidence: 99%
“…In this specific use case, with all coils energized the benefit of closer proximities provided by hexagonal coils is increased coupling cancellation. To reiterate, proximity effects such as mutual coupling [29], degraded Q and distorted current waveforms, caused by unwanted coil to coil interaction, is mitigated by our ability to power down, ground non-energized coils and control individual coil current levels. It has also been reported in the literature that hexagonal shaped coils have more uniform fields than that of circular or square coils [39].…”
Section: B Controllable Depth Of Penetrationmentioning
confidence: 99%
“…Several approaches use a flat or curved grid of approximately equally sized loops (Han, Chun, Lee, & Lee, 2004; Ho, et al, 2009; Laudani, et al, 2015; Ruohonen & Ilmoniemi, 1998; Ruohonen, et al, 1999; X. Wang, Chen, Guo, & Wang, 2005).…”
Section: What Are the Major Developments In Tms Technology?mentioning
confidence: 99%
“…The mutual coupling could induce currents at adjacent coils, which could influence the spatial localization of the stimulation when the coil array has a high magnetic coupling configuration. However, the coupling effect can be compensated by proper control of the charge voltages [9]. When the figure-of-8 coils have the current of the same direction, different type has different focality.…”
Section: Figure-of-8 Coilsmentioning
confidence: 99%